Investigating access and use of digital tools for agriculture among rural farmers: A case study of Nkomazi Municipality, South Africa - Olorunfemi Oluwasogo David; Mamiane Thapelo Austin; Matiwane Mona Ben (Open Agriculture)
The study examined the access and utilization of digital tools for agriculture among rural farmers in Nkomazi, Mpumalanga, South Africa. Data were collected from 120 rural farmers who were purposively sampled in Nkomazi Municipality. Information was gathered from the respondents through enumerator-administered structured questionnaires. The data were analyzed descriptively using percentages, means, and ranks, and multiple linear regression was employed to analyze the influence of the farmers’ socio-economic characteristics on their utilization of digital tools. The findings reveal that the farmers had an average age of 45.81 years. Approximately half (50.9%) of the farmers had no formal education or only completed primary education, and the average years of farming experience was 8.62 years. Overall, the farmers had access to traditional digital tools and apps such as radio, television, and smartphones. However, their utilization of these tools and apps, especially modern digital tools such as WhatsApp (43.3%) and Facebook (37.5%) for agricultural purposes, was still relatively low. This can be attributed to various challenges highlighted by the farmers, including insufficient skills and training, high costs of tools and apps, and issues related to network coverage. The educational level and cosmopoliteness of the farmers were identified as key socio-economic factors influencing the utilization of digital tools among the respondents. It is recommended that the farmers receive education and training on the use of modern digital tools and apps to enhance their ability to leverage them effectively and efficiently for the benefit of their agricultural enterprise.